1999
DOI: 10.1094/cchem.1999.76.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Study of Water in Dough Using Nuclear Magnetic Resonance

Abstract: Cereal Chem. 76(2):231-235The amount and state of water play an important role in the preparation and properties of wheat flour doughs and their products. A new method for presentation and analysis of relaxation time measurements of protons in dough is described in this article. This new method acknowledges a continuous probability distribution of protons having different relaxation times in heterogeneous systems such as dough, which is dramatically different from the conventional discrete methods that rely on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 25 publications
(28 reference statements)
4
59
0
Order By: Relevance
“…Experimental error of the mean of the distributions was approximately 2% for all samples studied. These compare reasonably well with T 2 relaxation values found in the literature for the same system (Assifaoui, Champion, Chiotelli, & Verel, 2006;Engelsen, Jensen, Pedersen, Norgaard, & Munck, 2001;Kim & Cornillon, 2001;Ruan, Wang, Chen, & Fulcher, 1999). The first distribution has been assigned to water that exhibits strong interactions with gluten and starch (Assifaoui et al, 2006;Engelsen et al, 2001;Kim & Cornillon, 2001;Ruan et al, 1999).…”
Section: Water Dynamics Of Thawed Flour-water Mixtures Probed By Nmrsupporting
confidence: 89%
“…Experimental error of the mean of the distributions was approximately 2% for all samples studied. These compare reasonably well with T 2 relaxation values found in the literature for the same system (Assifaoui, Champion, Chiotelli, & Verel, 2006;Engelsen, Jensen, Pedersen, Norgaard, & Munck, 2001;Kim & Cornillon, 2001;Ruan, Wang, Chen, & Fulcher, 1999). The first distribution has been assigned to water that exhibits strong interactions with gluten and starch (Assifaoui et al, 2006;Engelsen et al, 2001;Kim & Cornillon, 2001;Ruan et al, 1999).…”
Section: Water Dynamics Of Thawed Flour-water Mixtures Probed By Nmrsupporting
confidence: 89%
“…frozen storage time for both soy and wheat dough varieties (Table 2). Although the observed T 1 times may be slightly less than actual T 1 spin-lattice values due to cross-relaxation behaviours (Watanabe, Fukuoka, & Watanabe, 1995), soy dough exhibited shorter T 1 times for the majority population at every time point, suggesting that the water molecules were more translationally and/or rotationally hindered than those in the wheat dough (Ruan et al, 1999). Literature on spin-lattice relaxation experiments in dough performed using high field NMR (>7.05 T, 300 MHz 1 H frequency) is sparse and, due to the strong dependence of T 1 relaxation times on field strength, it is not appropriate to compare results to data collected at low field strength (ca.…”
Section: Discussionmentioning
confidence: 81%
“…4.5-5.0 ppm; Lodi, Tiziani, & Vodovotz, 2007) vs. delay time was used to fit an exponential rise to maximum equation to attain T 1 relaxation times. The relaxation curves fit best to a double exponential equation (1), thereby distinguishing two distinct 1 H water populations [attributed to different water populations (Ruan et al, 1999)]. …”
Section: T 1 and T 2 Relaxation With Solution State Nmrmentioning
confidence: 99%
“…It was revealed that 1 H transverse relaxation time T 2 is able to reflect the availability and mobility of water inside the foods [16,17]. Monolayer of water molecules is almost immobilized, and it behaves so in many aspects (also in NMR spectroscopy) as part of a solid.…”
Section: Journal Of Food and Nutrition Researchmentioning
confidence: 99%